Benteng Alla: Islamization of the Ancestral Land by DI/TII - A. Rahman (Diponegoro University, 2020)
DI/TII movement, which lasted for approximately 15 years in South Sulawesi, targeted the inland areas identical to forests. This fact certainly made it difficult for TNI (Indonesian National Armed Forces) to trace the presence of Kahar Muzakkar's troops. Benteng Alla which was located in the interior part of Enrekang also became a target. The village, which was directly adjacent to Tana Toraja, then transformed into a pathway used by DI/TII to expand its territory to Tana Toraja without going through the main road. This area was then completely controlled by DI/TII, in which the Islamic laws enforced there. Islamic law enforcement around Benteng Alla caused the neglect of Aluk Todolo teachings previously adopted by the community. Moreover, DI/TII also implemented economic engineering in Benteng Alla by utilizing zakat. One of the objectives of the economic engineering implementation was to prevent the community from visiting the city while still paying attention to the education of Benteng Alla communities who had become part of their movement. However, the communities then became the target of Indonesian National Armed Forces operations that came from Toraja. As a result, Benteng Alla was emptied for several years. This article is made by applying four methods in writing history with the aim of analyzing the significance of Benteng Alla's position during the DI/TII period and to pave the pathways passed by DI/TII so that this movement spread to Southeast Sulawesi.